2015
DOI: 10.1002/esp.3734
|View full text |Cite
|
Sign up to set email alerts
|

Joint isotopic mass balance: a novel approach to quantifying channel bed to channel margins sediment transfer during storm events

Abstract: The important role of floodplains and the broader riparian zone in providing temporary storage for a large fraction of the annual sediment load of rivers is well established, but this understanding is largely based on observations of the long-term average behavior of the catchment. Here we combine measurements of the fallout radionuclides 7 Be and 210 Pb and the stable isotopes of hydrogen in water to quantify fine sediment mobilization and storage in a stream and its channel margins during individual intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 76 publications
5
26
0
Order By: Relevance
“…During rainfall events that occur at times of relatively low flow (e.g., summer thunderstorms), fluvial deposits can be above water level at onset of rain where they come into contact with fallout nuclides. These deposits can become a net sink of FRN activity (Underwood et al, ). We propose that these in‐channel deposits are tagged with FRNs and exit the channel during the event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During rainfall events that occur at times of relatively low flow (e.g., summer thunderstorms), fluvial deposits can be above water level at onset of rain where they come into contact with fallout nuclides. These deposits can become a net sink of FRN activity (Underwood et al, ). We propose that these in‐channel deposits are tagged with FRNs and exit the channel during the event.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its short half‐life, 7 Be would be delivered to the channel outlet in fast hydrologic pathways, such as channel interception or overland flow. Recent research in forested and forest‐influenced watersheds in the eastern United States suggests the importance of channel interception of FRNs for sediment studies and indicates that 7 Be can bind to sediments within the stream channel, such as deposits and suspended particulate material, during the course of a precipitation event (depicted in Figure b; Karwan et al, ; Kaste et al, ; Underwood et al, ). In the Connecticut River Basin, Kaste et al () found summer thunderstorms delivered 7 Be from precipitation to the streambed and in‐channel deposits, which remained stored in the channel until subsequent higher flows remobilized the 7 Be‐tagged sediments and transported them out of the reach.…”
Section: Introductionmentioning
confidence: 99%
“…The example of the investigation of the CSC has been presented on the example of the braided-wandering river. The presented approach differs from other studies of river sediment connectivity on the basis of detailed mapping (Harvey, 2002;Hooke, 2003;Hooke, 2004), textural variability of sediments along the rivers (Cudden & Hoey, 2003;Rice & Church, 1998), searching relation between particle path length distributions and landforms (Pyrce & Ashmore, 2003), measurements of sediment transport using tracers (Konrad, Booth, Burges, & Montgomery, 2002;Reid, Lane, Berney, & Holden, 2007;Underwood, Renshaw, Magilligan, Dade, & Landis, 2015), application of more formalized approaches and direct field measurements (e.g., Klösch et al, 2015;Piqué et al, 2014) or sediment pulses (e.g., Yantao et al, 2003;Zunka, Tullos, & Lancaster, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Large storms generate sufficient surface runoff to deliver sediment from the uplands to the stream. In forest catchments overflow typically occurs only in a small fraction of the catchment, and it is most likely to occur very close to the stream (Underwood et al, 2015). Reforestation may increased the return period of peak flow and peak sediment yield (Keesstra, 2007).…”
Section: Discussionmentioning
confidence: 99%